Digitalization of Self-Development Skills Assessment through the ASSES-ABK Application in Inclusive Schools - Mirnawati Mirnawati; Amka Amka; Susanti Dewi Juwita; Najia Rania Alfa; Amanah Amanah (AL-ISHLAH: Jurnal Pendidikan, 2026)
Although digital assessment is increasingly utilized in educational settings, digital instruments specifically designed to assess self-development skills of students with special educational needs in inclusive schools remain limited. This study aimed to develop and conduct an initial validation of the ASSES-ABK application as a digital instrument for assessing self-development skills and supporting the development of Individualized Education Programs (IEPs). The study employed a design-based research (DBR) approach integrated with the ADDIE development framework, encompassing the phases of needs analysis, design, development, implementation, and evaluation. Data were collected through needs assessment, expert validation, teacher and parent perception questionnaires, application log data, and a limited field trial involving five students with special educational needs, five special education teachers/special assistant teachers, five classroom teachers, and five parents from an inclusive school. The application integrates standardized assessment indicators with a 0–4 scoring scale, automated assessment history storage, progress visualization, and digital reporting features. Expert validation results indicated that the prototype was feasible for implementation, with mean scores of 3.60 for content appropriateness, 3.70 for feature relevance, and 3.40 for interface clarity and usability. Descriptive findings from the field trial showed that the average assessment time decreased from 27.4 minutes using manual assessment procedures to 12.6 minutes with ASSES-ABK, representing a reduction of approximately 54.0%. Teachers and parents also reported improved perceptions of assessment consistency, result transparency, and parental involvement following the use of the application. As the field trial was limited to a single school and only five students, the findings should be interpreted as preliminary evidence of practicality rather than broadly generalizable evidence of effectiveness. ASSES-ABK offers a practical digital assessment model that assists teachers in documenting self-development skills more systematically and utilizing assessment data to support IEP development in inclusive school settings.